Whole body vibration and drop jumps induces post-activation performance enhancement - George Dallas; Serge S. Colson; Panagiotis Pappas; Costas Dallas; Giorgos Paradisis (Termedia Publishing House, 2022)
Purpose Many studies have investigated the effect of whole body vibration (WBV) exercise on post-activation potentiation. It was reported that an intervention protocol of WBV combined with 5 drop jumps (DJs) led to an increase in twitch force, suggesting the occurrence of post-activation potentiation. The purpose of this study was to examine the acute effect of different warm-up interventions on countermovement jump (CMJ) performance by recording jump height, power, and take-off velocity in gymnasts. Methods Overall, 10 adult gymnasts (mean age: 22.80 ± 1.75 years; body mass: 61.92 ± 8.65 kg; body height: 170.10 ± 8.65 cm) with 16.35 ± 5.68 years of training experience volunteered to participate in this study. The interventions were (i) WBV, (ii) no vibration, (iii) DJs, and (iv) WBV combined with DJs (WBVDJ). Over 4 distinct randomized testing sessions, the gymnasts performed pre-intervention tests comprising 3 CMJs, followed by one of the 4 interventions; after 8 min, they performed another set of 3 CMJs. Results A significant interaction was observed between interventions for jump height and take-off velocity, leading to improvements (+4.82%, p < 0.05; +2.50%, p < 0.05, respectively) after WBVDJ only. No significant improvements were noted for WBV, DJs, or no vibration interventions. The implementation of WBVDJ was an effective stimulus leading to post-activation performance enhancement of CMJ in gymnasts. Conclusions The WBVDJ intervention increased jump height of CMJ performance and take-off velocity of lower limbs. In addition, WBVDJ led to greater performance improvement compared with DJ intervention.